Penyajian Informasi Sarana dan Prasarana Berbasis Sistem Informasi Geografis di Kecamatan Tanete Raittang Kabupaten Bone - Asdianti, Asdianti (LaGeografia, 2018)
The aim of research to determine: 1) methods of presenting information based GIS infrastructure, 2) distribution facilities and infrastructure, and 3) The condition of facilities and infrastructure. This research was conducted by survey method. The study population includes building government infrastructure, economy, education, and worship kesehatanm with purposive sampling technique. Qualitative descriptive analysis based geographic information system. The results showed: 1) Presentation of information facilities and infrastructures based GIS is done by describing the results of the survey in the field with the attribute data (tables of research) and spatial data in the form of a map that details of each infrastructure that includes government, the economy, education, health, and worship that is able to answer all of the existing problems. 2) Distribution of facilities and infrastructure tend to converge on the village as well as for economic infrastructure centered in the Village Watampone, facilities and infrastructure pendidikakan centered in the Village Blue. 3) The condition of facilities and infrastructure are categorized in very good condition with aspects of SSR assessment in the form of the building functioned as the function of the establishment, fitness for use, facilities support adequate and good maintenance.